2019
DOI: 10.3329/bjp.v14i4.42499
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant activity of Citrus limetta leaves in mice using battery of behavior models modulating via serotonergic systems 

Abstract: The methanolic extract of Citrus limetta leaves was estimated in the present study for antidepressant activity. This activity was evaluated by using the rat behavioral model i.e. forced swimming and tail suspension model for 14 days, with estimation of neurotransmitters in animals brain. The sedative effect was evaluated by actophotometer. The extract (200 mg/kg) administered orally showed significant (p<0.05) decrease in immobility time against the standard drug fluoxetine (20 mg/kg, i.p), and imipramine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…These outcomes specify that the antidepressant activity of AEAES involves the 5HT 2 serotonergic receptors interaction but not 5HT 1 and 5HT 3 receptor interactions. Few studies reported the interaction of either an extract or flavonoids with serotonergic receptors in producing an antidepressant-like effect on the monoaminergic system, indicating a comparable mode of action of these compounds 6,17,21,22 .…”
Section: Fig 3: Effect Of Aeaes Pretreated With Opioid Receptor Block...mentioning
confidence: 99%
“…These outcomes specify that the antidepressant activity of AEAES involves the 5HT 2 serotonergic receptors interaction but not 5HT 1 and 5HT 3 receptor interactions. Few studies reported the interaction of either an extract or flavonoids with serotonergic receptors in producing an antidepressant-like effect on the monoaminergic system, indicating a comparable mode of action of these compounds 6,17,21,22 .…”
Section: Fig 3: Effect Of Aeaes Pretreated With Opioid Receptor Block...mentioning
confidence: 99%
“…Further pharmacological and biological activities were recently discovered such as anticoagulant and antithrombotic effects (Siritapetawee et al, 2020) and the antiviral activity against the virus of tomato yellow leaf curl (Zhao et al, 2021). Several medicinal plants as Agaricus blazei (Haq et al, 2019), Capsicum annuum (Jawad et al, 2017), Citrus limetta (Kaur et al, 2019), Glycyrrhiza glabra (Dhingra and Sharma, 2006), Hypericum perforatum (Tian et al, 2014), Mondia whitei (Oketch-Rabah, 2012), Salvia officinalis (El Gabbas et al, 2018) were reported to possess antidepressant-like effect. There is a need to find new antidepressant biomolecules to respond to the increase in the incidence of anxiety as a modern disease and oxidative stress as a major source of different diseases.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Many cosmetic companies use Citrus limetta as a key ingredient in their products as it has antioxidant, antibacterial, and detoxifying properties which are useful against hyperpigmentation and tanning. [11] Citrus limetta leaves extract was also reported to be effective as an antidepressant [12] and antihypertensive. [13] The citric acid in leaves extract of citrus limetta acted as a reducing and capping agent in the green synthesis of TiO 2 nanoparticles.…”
mentioning
confidence: 99%